2021
DOI: 10.3748/wjg.v27.i42.7299
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy-related colonic ischemia

Abstract: Colonoscopy is a risk factor for colon ischemia. The colon is susceptible to ischemia due to its minor blood flow compared to other abdominal organs; the etiology of colon ischemia after colonoscopy is multifactorial. The causative mechanisms include splanchnic circulation impairment, bowel preparation, drugs used for sedation, bowel wall ischemia due to insufflation/barotrauma, and introduction of the endoscope. Gastroenterologists must be aware of this condition and its risk factors for risk minimization, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The small bowel, which is a large part of the intestines, is inaccessible; it lacks the sensitivity and specificity needed to detect more subtle ischemic changes; the observed ischemia changes do not indicate whether the cause of ischemia is due to occlusive or non-occlusive; the observed mucosal necrosis does not always correspond to transmural necrosis. Moreover, it was also reported that colonoscopy was one of the risk factors for colon ischemia ( Sadalla et al, 2021 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…The small bowel, which is a large part of the intestines, is inaccessible; it lacks the sensitivity and specificity needed to detect more subtle ischemic changes; the observed ischemia changes do not indicate whether the cause of ischemia is due to occlusive or non-occlusive; the observed mucosal necrosis does not always correspond to transmural necrosis. Moreover, it was also reported that colonoscopy was one of the risk factors for colon ischemia ( Sadalla et al, 2021 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…If there is suspicion of an issue in the colon, large intestine, or the lower part of the small intestine, a colonoscope is inserted through the rectum. Colonoscopy is particularly recommended for individuals who cannot undergo a contrast injection, especially those with allergies or kidney problems [47].…”
Section: Colonic Ischemiamentioning
confidence: 99%
“…The primary test for secondary CRC prophylaxis is a colonoscopy [8,9]. This examination involves viewing the large intestine from the lumen side using a thin, flexible tube (colonoscope) with a camera on the end, through which the physician obtains an image of the intestinal mucosa on the monitor.…”
Section: Screeningmentioning
confidence: 99%